A noção de libertação política no pensamento de Paulo Freire - Fochezatto, Anadir (2012)
The aim of this research is a comprehensive approach about the notion of politics liberation in Paulo Freire s thought. With this purpose, we present, first, some experiences that have influenced Paulo Freire s forging and its philosophical political thought, in a view that human beings can not be understood outside the social history context. This way we begin by analyzing the conception of man and dialogicity, due to it is highly valued by our author. Then we deal with the issues of education and revolutionary practice as the basis to the liberation of consciousness and a way to the transformation. Finally, we handle about the previous discussion in order to delineate the notion of politics liberation and their constituents of Paulo Freire s thought. After all, we managed to list four primary pillars that support this notion. They are: awareness of self, of others and of reality, coherence, solidarity and organization.